PERAN PEMUDA DALAM MENINGKATKAN EKONOMI KREATIF PADA KEGIATAN PESANTREN KILAT RAMADHAN PRAMUKA KOTA SIBOLGA - Hendra Sahputra (Universitas Pahlawan Tuanku Tambusai, 2022)
Universities carry out three main tasks of academic activities, namely providing education, research, and community service, which has been known as the Tridarma of Higher Education. Community Service is an activity of applying science and technology which includes development, dissemination and civilizing of science and technology among youth in the context of improving the creative economy. According to estimates from the Central Statistics Agency, it is estimated that Indonesia will experience a demographic bonus during the years 2030-2040. This means that in this period, the condition of the Indonesian people will be dominated by the productive age compared to the non-productive age. It is projected that as many as 297 million Indonesians are of productive age and youth are part of the productive age population, which is dominated by the age of 28-29 years. One of the roles of youth in development, among others, can be seen from the employment side. Youth capacity and productivity are expected in an optimal labor market and able to drive economic activity, for this reason it is necessary to understand the benefits of the creative economy among people in order to increase creativity and create new jobs. The method of implementing the activities carried out was by providing socialization to participants of the Ramadhan Scout Islamic Boarding School in Sibolga City which consisted of 40 high school students throughout Sibolga City. The output of this activity is expected that participants can increase creativity and creativity in the creative economy business based on the ability and process of creating something based on ideas, ideas and creativity. Keywords: Higher Education, Youth, Creative Economy